Association between dietary vitamin C and telomere length: A cross-sectional study - Cai, Yuan; Zhong, Yu-di; Zhang, Hao; Lu, Pei-lin; Liang, Yong-yi; Hu, Biao; Wu, Hui (Frontiers in Nutrition, 2023)
Background Currently, telomere length is known to reflect the replication potential and longevity of cells, and many studies have reported that telomere length is associated with age-related diseases and biological aging. Studies have also shown that vitamin C acts as an oxidant and free radical scavenger to protect cells from oxidative stress and telomere wear, thus achieving anti-aging effects. At present, there are few and incomplete studies on the relationship between vitamin C and telomere length, so this study aims to explore the relationship between vitamin C and telomere length. Method This study used cross-sectional data from the NHANES database from 1999 to 2002 and included 4122 participants aged 45 years and older. The correlation between vitamin C and telomere length was assessed using a multiple linear regression model, and the effect of dietary vitamin C on telomere length was obtained after adjusting for confounding factors such as age, gender, race, BMI, and PIR. Result This cross-sectional study showed that vitamin C was positively correlated with telomere length, with greater dietary vitamin C intake associated with longer telomeres (β : 0.04 95%Cl: 0.01-0.06 P: 0.002). Conclusion The study suggests that there is a direct or indirect interaction between dietary vitamin C and telomere length, which may have certain clinical significance. Keywords Telomere length, vitamin C, interaction, cross-sectional studies